How do productivity, minimum wage and exogenous variables affect urban unemployment in Ecuador? - Avellán Solines, Guillermo (2018)
Ecuador’s 2016 recession demonstrated the vulnerability of its economy due to volatility of exogenous variables such as oil prices and US dollar exchange rate. Additionally, annual increases in the minimum wage and labor productivity growth had an impact on the labor market during the last decade. This research estimates the effects of labor productivity, real minimum wage and exogenous factors—oil prices and US dollar exchange rate—in Ecuador’s urban unemployment rate between June 2007 and June 2017. The main conclusions of this study are as follows: i) a reduction of oil price and an appreciation of the US dollar cause an increase in the urban unemployment rate; ii) an increase in the real minimum wage, not taking into account labor productivity, provokes an increase in the urban unemployment rate; iii) an increase in labor productivity generates an increase in the urban unemployment rate in the short-term consistent with recent literature; iv) finally a distributed lag model including these four variables explains 64% of the change in the urban unemployment rate between 2007 and 2017.